MORBIDITY AND MORTALITY, STRUCTURE AND RESULTS OF CERVICAL CANCER SCREENING IN THE REGIONS OF KAZAKHSTAN - Arman Khozhayev; Dilnaz Mukhametova; Rudaba Majikova; Laura Bissenova; Oryngul Rakhmetova; Kanat Bayanov; Gulmira Iskakova; Kaisar Ozganbay (Research Retrieval and Academic Letters, 2023)
The paper discusses the morbidity and mortality rates from cervical cancer by regions, describes in detail the currently used screening methodology and the results of this preventive examination of the female population of our country. A detailed step-by-step algorithm is presented and the principles of organization and diagnostic capabilities of this method for the active detection of cervical cancer in clinically asymptomatic individuals are reflected. It is shown that in order to achieve a highly effective result, strict adherence to the methodology of this type of screening is necessary.